IMPLICATIONS FOR LOADING JURIDICAL LIABILITY RIGHTS UNDER POWER OF ATTORNEY MAKE HYPOTHEEK RIGHTS (SKMHT) PROCEDURAL DEFECTS - Rustam, Riky; Suwardiyati, Rumi (Nurani, 2021)
The credit agreement is an agreement in principal to followedby the additional treaty of guarantee. With regard to guarantees for immovable objects using mortgage rights. In banking practice related to credit agreements, it is inseparable from a power of attorney to impose mortgage rights (SKMHT). Those who have the authority to make the power of attorney are notaries. In making deeds in their daily lives, a notary is obliged to pay attention to the rules for making authentic deeds. Making authentic deeds must meet formal requirements, material requirements and external requirements in making them. If one of these conditions is not fulfilled, it can cause the deed to be degraded or decrease in the status of the deed, which was initially considered an authentic deed to become an underhand deed. In connection with the power of attorney imposing mortgage rights (SKMHT), Notaries who have cooperation with banks will make the power of attorney every day. It is possible that the number of deeds made makes the notary forget to sign the deed he has made. The signatures of the parties that are in the power of attorney already exist, but the signature of the Notary who ratifies the power of attorney is not there. This is possible until the Notary's death, the deed he has made has not been signed. If the Notary passes away and the deed he has drawn up has not been signed and a dispute arises, how will the deed be authenticated. The research objective is to analyze the authentication of the power of attorney to impose mortgage rights (SKMHT) that have not been signed by a notary public. The method used is juridical normative with a statutory approach and a conceptual approach. The conclusion of the research is that the notary of the SKMHT deed has not been signed by the notary until the Notary concerned dies, violating the formal requirements of the authentic deed This resulted in the power of attorney imposing mortgage rights (SKMHT) to be null and void by law while still giving the injured party the right to claim compensation from the Notary who had harmed the party.